Sources of academic stress among Iranian adolescents: a multilevel study from Qazvin City, Iran - Z. Hosseinkhani; H. R. Hassanabadi; M. Parsaeian; M. Osooli; S. Assari; S. Nedjat (SpringerOpen, 2021)
Abstract Background Academic stress can cause mental and physical problems and affect adolescents' healthy development. This study aimed to estimate academic stress and explore its sources at the individual- and school levels among school-going adolescents in the city of Qazvin, Iran. Results This cross-sectional study used a stratified cluster sampling to recruit 1724 students aged 12-19 years from 53 schools in Qazvin City. Data were collected using a validated self-administered questionnaire. The mean academic stress score was 45.7 (95% CI 45.2, 46.3). The stress level was statistically higher among older 47.5 (95% CI 46.7, 48.3) than younger 44.1 (95% CI 43.4, 44.9) adolescents. The main academic stressors included: future uncertainty 69.7 (95% CI 68.8, 70.7), academic competition 58.5 (95% CI 57.3, 59.6), and interaction with teachers 56.1 (95% CI 55.3, 56.9). Gender, educational period, school type, family socioeconomic status, and father's education were associated with academic stress. Conclusions We conducted a multilevel study using a random sample of male and female students in the city of Qazvin, Iran. Results indicated moderate levels of stress among Iranian adolescents. The academic stress was associated with several individual and school-level variables. Students and their families and teachers need education on stress prevention methods and coping mechanisms. Future research should focus on developing and testing multilevel policies and interventions to improve students' mental health and academic performance.